The Impact of Islamic Finance Development on Economic Performance: A Driscoll-Kraay Panel Analysis of 30 Countries - Eko Gondo Saputro (Universitas Islam Negeri (UIN) Walisongo Semarang, 2026)
Purpose - This study investigates the relationship between Islamic finance development and economic performance in 30 countries during the period 2014 to 2023. Method - This study employs a panel regression approach, utilizing Driscoll-Kraay standard errors to address cross-sectional dependence, heteroskedasticity, and autocorrelation. Economic performance is proxied by real GDP at constant prices, while Islamic finance development is measured using the Islamic Finance Country Index (IFCI). Additionally, FDI net inflows, unemployment rate, and the HDI serve as control variables. Result - The findings reveal a significant positive link between Islamic Finance development (IFCI) and economic performance in both models. HDI has a strong positive effect in both models, while the unemployment rate affects only model 2 negatively. FDI is not significant in either model. Implication - This study suggests stronger institutional and regulatory support for Islamic finance development. Clear policy, strong governance, and readiness help to maximize Islamic finance development's positive impact on economic performance. Originality - This study extends the literature by employing the Islamic Finance Country Index (IFCI) as a comprehensive indicator of Islamic finance development across countries. Furthermore, it provides novel cross-country evidence on the relationship between Islamic finance development and economic performance in 30 countries. Keywords: Economic Performance, Islamic Finance Development, Islamic Finance Country Index (IFCI), Panel Regression Model, Driscoll-Kraay